Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2020)
I have to honestly admit that writing this editorial feels very different from writing the one for the December of 2011 when Studies in Second Language Learning and Teaching had just completed its first year of existence. At that time, I was feeling a lot of uncertainty and trepidation about the future of the journal, wondering whether it would survive beyond the first year or two as well as whether it would stand a chance of becoming internationally recognizable. Today the situation is very different. Even though this has been an unprecedented year because of the COVID pandemic with all the havoc it has been wreaking all over the world, 2020 has proved to be exceptionally gracious to SSLLT. For one thing, not only has the journal survived and it is now turning 10 years of age, but it has also managed to secure its place among the most influential journals in the field, as can be seen, for example, from its ever-increasing indices in Scopus. Even more importantly, SSLLT has at last been included in some of the databases in Web of Science, most notably Social Sciences Citation Index (SSCI) and Journal Citation Reports Social Sciences (JCRSS). Needless to say, we have been waiting for this momentous turn of events for quite a few years and now we cannot wait again to find out the impact factor for the journal, which should be announced some time in 2021. Once again, I cannot stress enough that the huge success of the journal is the outcome of the contribution of numerous individuals, in particular the consecutive associate editors, authors, reviewers, as well as editors of special issues. All of this certainly calls for a celebration and it is our intention to do so by organizing a conference that would bring together all those who have been involved in SSLLT and supported it from its inception, in whatever capacity this might have happened. We are sincerely hoping to be able to hold this event in October 2021 and will be sending out a call for papers some time in December. We do realize that the pandemic can foil any plan now, but we are determined to celebrate the success of the journal. Should autumn 2021 turn out to be unfeasible, we will be aiming for spring 2022 and we are very confident that sooner rather than later we will be able to finally meet face-to-face to discuss key issues involved in the process of second language learning and teaching. While there is surely nothing wrong with online conferences, I am convinced that we would all rather have a chance to talk in person at along last and we will do our best to make this happen. One thing is for sure, whatever the timing, the Faculty of Pedagogy and Fine Arts in Kalisz, Adam Mickiewicz University, Poland, will be the venue for this event. After all, this is where the idea for SSLLT was conceived well over 10 years ago and where the journal has been published from the get-go.